2006
DOI: 10.2353/ajpath.2006.060265
|View full text |Cite
|
Sign up to set email alerts
|

Invasive Trophoblasts Stimulate Vascular Smooth Muscle Cell Apoptosis by a Fas Ligand-Dependent Mechanism

Abstract: During pregnancy, trophoblasts migrate from the placenta into uterine spiral arteries, transforming them into wide channels that lack vasoconstrictive properties. In pathological pregnancies, this process is incomplete. To define the fundamental events involved in spiral artery remodeling, we have studied the effect of trophoblasts on vascular smooth muscle cells (SMCs). Here we demonstrate for the first time that apoptosis of SMCs can be initiated by invading trophoblasts. When trophoblasts isolated from norm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
109
1
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 139 publications
(114 citation statements)
references
References 46 publications
3
109
1
1
Order By: Relevance
“…We have previously demonstrated that primary CTB and trophoblast cell lines can initiate endothelial and SMC apoptosis in spiral arteries via the Fas/Fas ligand pathway, and have proposed that a trophoblastdependent apoptotic mechanism contributes to endothelial and SMC loss during remodeling in pregnancy. 10,11 The current study identifies TRAIL as another important apoptotic ligand produced by trophoblast, that is able to induce SMC apoptosis. Here we propose that activation of the TRAIL pathway also contributes to SMC loss during spiral artery remodeling in human pregnancy.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We have previously demonstrated that primary CTB and trophoblast cell lines can initiate endothelial and SMC apoptosis in spiral arteries via the Fas/Fas ligand pathway, and have proposed that a trophoblastdependent apoptotic mechanism contributes to endothelial and SMC loss during remodeling in pregnancy. 10,11 The current study identifies TRAIL as another important apoptotic ligand produced by trophoblast, that is able to induce SMC apoptosis. Here we propose that activation of the TRAIL pathway also contributes to SMC loss during spiral artery remodeling in human pregnancy.…”
Section: Discussionmentioning
confidence: 99%
“…10,11 Images were analyzed using ImagePro Plus (Media Cybernetics, Silver Spring, Md). Details are provided in the online data supplement.…”
Section: Time-lapse Microscopymentioning
confidence: 99%
See 1 more Smart Citation
“…Remodeling of the spiral arteries involves derangement of their vascular smooth muscle layer and loss of their endothelial lining. 81,82 This results in conversion of the spiral arteries from tightly coiled vessels to low resistance, wide-bore conduits that are not tonically active. In preeclampsia, spiral artery remodeling is incomplete, with some vessels retaining portions of their smooth muscle and others being totally unmodified.…”
Section: Uterine Arterial Adaptations and Responses In Preeclampsia Smentioning
confidence: 99%
“…The dogma is that invasive EVTs, which detach from placental villous columns anchored to the decidua, mediate the destruction of the vascular wall, either from within the vessel (endovascular (v)EVTs) or from the surrounding decidual stroma (interstitial (i)EVTs). In vitro studies demonstrate that isolated trophoblast cells are capable of triggering apoptosis of VSMCs, potentially via trophoblast-derived Fas ligand and tumor necrosis factor-␣-related apoptosis-inducing ligand, 5,6 and EVTs produce matrix metalloproteinases (MMPs) capable of cleaving substrates in the vascular wall. 7,8 However, apoptotic vascular cell death has not been demonstrated in remodeling vessels in vivo 9 and there is accumulating evidence for remodeling events that precede the appearance of EVT.…”
mentioning
confidence: 99%